KOMPETENSI LINTAS BUDAYA DALAM INTERNASIONALISASI UMKM DI INDONESIA SEBUAH AGENDA PENELITIAN - Kaukab, Elfan (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2017)
Cross-cultural competence as an approach in this paper enables Micro, Small, and Medium Enterprises (MSMEs) to work or respond effectively across cultures in ways that the values, beliefs, traditions, and customs are recognized. This study uses Jaccarino & Kendall (2004) empirical model to understand the cross-cultural competence process in an organization. The model consists of four elements: cultural awareness, skill development, development planning, and organization strategy. Moreover, this paper explores the roles of cross-cultural competence on the MSMEs internationalization process.